A luta em defesa da Sociologia no Ensino Médio: 1996-2007 : um estudo sobre a invenção das tradições - Romano, Fábio Geraldo [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
This paper aims at analyzing the political struggles of agents, better known as entities (such as unions, confederations, professional associations, scientific societies, faculty institutions) and professionals in social science areas (teachers, sociologists, professors etc), for compulsory inclusion of Sociology (and in a smaller circumstance, Philosophy) as subjects in the High School syllabus in the period ranging from 1996 - a very important date due to the publication of the New Law of National Education Policy Program (LDB 9394/96) - to 2007, when the mentioned subjects have been definitely included in the High School syllabus in almost all national territory. More specifically, it is a research that seeks to understand the political dimension of this subject institutionalization in an equally very specific teaching level: Sociology in High School Education. As to methodology, the available documentation published during the focused period was largely analyzed: they were academic thesis and dissertations, articles, legislation, virtual forums, entities bulletins, communication boards, newspapers articles, among others. The hypothesis defends that in order to be considered valid and reach the objectives in this period of over a 10-year-struggle , the agents (entities and professionals) of Sociology - being now in a very different social situation from Philosophy - which is, itself, an heir to a legitimate tradition of 25 centuries - had to create a tradition for the subject. It was with this creation of a tradition for Sociology partial success that both the processes of school institutionalization and the pursuit of legitimacy as an autonomous and relevant subject among the other fields of knowledge obtained success

Este estudo tem como objetivo analisar a luta política dos agentes, isto é, das entidades (sindicatos, confederações, associações profissionais, sociedades científicas, instituições acadêmicas) e dos profissionais da área de ciências sociais (professores, sociólogos, acadêmicos etc.) pela inclusão obrigatória da Sociologia (e em menor medida da Filosofia) como disciplina no currículo do Ensino Médio (EM) a partir de 1996 - data importante devido à publicação da Nova Lei de Diretrizes e Bases da Educação Nacional (LDB 9394/96) -, até 2007, quando as disciplinas citadas foram definitivamente incluídas no currículo do Ensino Médio em quase todo o território nacional. Mais especificamente, trata-se de uma pesquisa que busca investigar a dimensão política da institucionalização de uma disciplina específica em um nível também específico de ensino: a Sociologia no Ensino Médio. Metodologicamente, analisamos a documentação disponível publicada durante o período em questão: teses e dissertações, artigos, legislação, fóruns virtuais, boletins das entidades, comunicações, matérias de jornal, dentre outros. A hipótese é a de que, para que tivessem legitimidade e alcançassem os seus objetivos nessa luta de mais de dez anos, os agentes (entidades e profissionais) da Sociologia - que se encontram numa situação social muito diferente da Filosofia, herdeira de uma tradição legítima de cerca de 25 séculos - tiveram que inventar uma tradição para a disciplina. E foi com o relativo sucesso da invenção de uma tradição para a Sociologia que obtiveram êxitos em seus processos de institucionalização escolar e de busca de legitimidade como uma disciplina autônoma e relevante entre os saberes escolares já instituídos
Keywords: Sociologia; Educação; Filosofia; Ensino médio; Tradição (Filosofia); Education